Acute effects of running over different height mini-hurdles on sprint kinematics in athletes - Makaruk, B. (Theory and Practice of Physical Culture, 2021)
The purpose of this study was to examine the influence of the height of mini-hurdles on the kinematics of sprinting in sprinters and jumpers. Twelve male athletes (mean ± SD, age: 21.5 ± 1.9 years, height 178.4 ± 5.1 cm, body mass 74.6 ± 6.4 kg) ran maximal flying sprint under 3 different conditions: with flat, medium and high mini-hurdles (0.5, 13 and 20 cm high, respectively). The obstacles were set from 20 to 40 m. The Optojump Next (Microgate, Italy) was used to assess running velocity, stride length, stride frequency, contact time and flying time. The analysis revealed that running velocity and stride frequency were significantly greater (p < 0.05) in the flat mini-hurdles condition compared to the high mini-hurdles condition. Stride length significantly increased (p < 0.05) in the high mini-hurdles condition when compared with the flat mini-hurdles conditions. There were no significant differences (p > 0.05) between the medium condition and the other conditions for all sprint kinematics. We suggest that coaches and practitioners should adjust the height of sprinting obstacle depending on training needs.